Program matrikulasi bahasa Arab pada pondok pesantren: Konsep dan relevansi - Ibrahim, Moh; Tamam, Abas Mansur (TAWAZUN: Jurnal Pendidikan Islam, 2024)
Pesantren education has distinct characteristics and features in its matriculation system compared to the matriculation system in public schools. There are fundamental differences that can be observed in several aspects, such as the dominance of religious education in the matriculation curriculum, the 24-hour implementation of matriculation, the pesantren curriculum, and educational elements that involve the mosque, dormitories, and kiai (religious teachers) as integral parts of the pesantren matriculation system. All of these aspects indicate that the matriculation system in pesantren is not the same as the commonly applied matriculation system in schools. To facilitate the matriculation process for students to achieve optimal results, matriculation is divided into several categories, including matriculation in congregational prayer, Quran recitation, evening study supervision, extracurricular lessons, sports activities, lectures (muhadharah), language discipline, discipline in leaving the campus, and discipline in campus life. In Arabic Language matriculation, there are four integrative approaches applied, namely: 1) Humanistic Approach, 2) Aural and Oral Approach, 3) Analysis and Non-Analysis Approach, and 4) Communicative Approach. By integrating these four approaches, it is expected to create an active, communicative, cognitively intelligent, and speaking-centered learning experience. Abstrak          Pendidikan pesantren memiliki karakteristik dan ciri khas matrikulasi yang berbeda dengan sistem matrikulasi di sekolah umum. Terdapat perbedaan mendasar yang dapat dilihat dari beberapa hal, seperti dominasi materi matrikulasi yang berfokus pada pendidikan keagamaan, pelaksanaan matrikulasi selama 24 jam, kurikulum pesantren, serta elemen-elemen pendidikan yang melibatkan masjid, asrama, dan kiai sebagai bagian integral dari sistem matrikulasi pesantren. Semua aspek ini menunjukkan bahwa sistem matrikulasi di pesantren tidaklah sama dengan sistem matrikulasi yang umum diterapkan di sekolah. Demi memfasilitasi proses matrikulasi santri agar mencapai hasil yang optimal, matrikulasi dibagi ke dalam beberapa kategori, termasuk matrikulasi dalam shalat berjamaah, membaca Al-Qur'an, pengontrolan belajar malam, pelajaran ekstrakurikuler, kegiatan olahraga, muhadharah (ceramah), disiplin bahasa, disiplin keluar kampus, dan disiplin kehidupan di dalam kampus. Dalam matrikulasi Bahasa Arab, terdapat empat pendekatan yang diterapkan secara integratif, yaitu: 1) Pendekatan Humanistik. 2) Pendekatan Aural dan Oral 3) Pendekatan Analisis dan Non Analisis 4) Pendekatan Komunikatif. Dengan mengintegrasikan keempat pendekatan tersebut, diharapkan dapat menciptakan pembelajaran yang aktif, komunikatif, cerdas secara kognitif, dan berpusat pada kemampuan berbicara.